Identification of test rig for a quarter car active suspension systems - Zulfatman, Zulfatman (2008)
System Identification approach can be used to estimate model and parameters of the passive system and hydraulic actuator of a test rig for quarter car active suspension system. The passive suspension system is consists of mass, spring, damper, and the hydraulic actuator. Identification of the systems is carried out based on the experimental works. The input to the system is an input signal to control the valve and output from the system are the output signals from the accelerometer and LVDT sensors. Input signal generation and data acquisitions process is controlled by using the LabView. In order to estimate the model and parameter, the data are processes using the System Identification Toolbox in Matlab. Since the system is modelled as a linear model, linear ARX model is utilised as a model structure. Model parameter estimation for the passive system and hydraulic actuator are performed using ARX221 and ARX631, respectively. Through the validation process, percentage of the best fit can be reached more than 90%, and the smallest LF, PFC and AIC criterions also can be reached, hence the model parameters of the systems is acceptable.